Coherent ultra-violet to near-infrared generation in silica ridge waveguides - Dong Yoon Oh (Nature Portfolio, 2017)
Continuum generation in optical fibres has enabled many applications, like optical frequency combs. Here, Ohet al. demonstrate controlled dispersive-wave generation in on-chip silica waveguides, which could have a similar impact on integrated devices.